2014
DOI: 10.1002/chp.21256
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Physician Reentry to Practice: Perceived Effects of Deployments on US Army Pediatricians’ Clinical and Procedural Skills

Abstract: US Army pediatricians are required to deploy for extended periods of time and have limited opportunities to practice the full range of their pediatric skills. This break in clinical practice is associated with a significant decline in perceived comfort with both routine and acute pediatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Most participants lack confidence, but there is no compelling evidence that competence is significantly affected by clinical inactivity. 14 A lack of confidence can reduce work rate and decrease practitioner wellbeing 14,37,38 but is not directly correlated with competence, particularly in the RTW setting. Formal assessment of competence was judged to be an unnecessary burden on both faculty and participants and was therefore not incorporated into the design of the course.…”
Section: Introductionmentioning
confidence: 99%
“…Most participants lack confidence, but there is no compelling evidence that competence is significantly affected by clinical inactivity. 14 A lack of confidence can reduce work rate and decrease practitioner wellbeing 14,37,38 but is not directly correlated with competence, particularly in the RTW setting. Formal assessment of competence was judged to be an unnecessary burden on both faculty and participants and was therefore not incorporated into the design of the course.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic procedures, once considered the surgeon's exclusive domain, are now practiced in almost all medical specialties [1]. Even though general pediatrics is not known to be a 'procedures-heavy' discipline, general pediatricians (GPeds) are expected to provide a medical home for their patients, which includes performing common procedures safely and effectively [2][3][4][5][6]. For nearly 30 years, common pediatric procedures have been incorporated into residency program curricula in the USA [7].…”
Section: Introductionmentioning
confidence: 99%
“…A 2002 JAMA review of the topic cited caretaking responsibilities, personal illness, career dissatisfaction, and alternative careers as common causes of physician reentry 1 . More recent studies suggest that changes in career paths into a non‐clinical position (such as administration), family issues, military deployments, and career dissatisfaction also contribute to physicians leaving the workforce voluntarily 8,12–13,15 . A survey of over 6000 pediatricians younger than 65 found that 12% of respondents indicated they had experienced a period of clinical inactivity lasting >12 months.…”
Section: Introductionmentioning
confidence: 99%